Multi-Brand Virtual Restaurant: Cloud Kitchen Business Model (Case Study of PT. Sagala) - Tualeka, Safarudin Hisyam (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The development of the Sharing Economy (SE) in the culinary field has experienced a significant increase during the pandemic era. The lockdown implemented in 2020 and the PPKM policy in 2021 have considerably affected the economy and behavior of the Indonesian people. Amid these challenging times, Cloud Kitchen has emerged as a notable innovation in the Food & Beverage (F&B) sector, particularly during the pandemic. The Multi Brand Virtual Resto business model, a variant of Cloud Kitchen, is gaining traction in Indonesia. This study aims to investigate the implementation of Multi Brand Virtual Resto in Indonesia, focusing on PT. Sagala as a case study. Interview findings reveal differences between Multi Brand Virtual Resto and Cloud Kitchen, with the former placing greater emphasis on the variety of products sold. PT. Sagala offers products with different brands for distinct product lines, all under one management. However, upon further analysis, Multi Brand Virtual Resto can be considered a form of Cloud Kitchen, specifically, The Rebel Foods model. In conclusion, PT Sagala's Multi Brand Virtual Resto business model is a manifestation of the Cloud Kitchen business model.